PENGARUH PERUBAHAN IKLIM TERHADAP PRODUKSI PERIKANAN TANGKAP DI KOTA BATAM MENGGUNAKAN ANALISIS REGRESI TIME SERIES - Faradiba Jabnabillah; Widya Reza (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2024)
This research aims to describe the influence of temperature, wind speed and rainfall on caught fish production in the city of Batam. The research method used is quantitative using a time series regression test which was analyzed from January 2019 to December 2022 with the variables analyzed being temperature (X1), wind speed (X2), rainfall (X3) and capture fisheries production (Y) . Partial test results show that the relationship between wind speed (X2) and rainfall (X3) on Y is negative, meaning that the higher the wind speed (X2) and rainfall (X3), the lower the production of caught fish (Y). Meanwhile, partial test results show that temperature (X1), wind speed (X2) and rainfall (X3) together have a significant effect on capture fisheries production (Y) in Batam city. The partial test results show that the significance value for the temperature variable (X1) is 0.25 > 0.05, which means that the temperature variable (X1) has no effect on capture fisheries production (Y) in Batam city. Meanwhile, the partial test results on the variables wind speed (X2) and rainfall (X3) obtained a value of 0.00 < 0.05, which means that the variables wind speed (X2) and rainfall (X3) have an effect on capture fisheries production (Y) in Batam city. Meanwhile, the results of simultaneous tests show that temperature (X1), wind speed (X2) and rainfall (X3) together have a significant effect on capture fisheries production (Y) in the city of Batam with a significance value of 0.00 < 0 .05. The coefficient of determination value in this study was 0.686. This means that weather changes have a proportion of influence on Batam city capture fisheries production of 68.6% while the rest is influenced by other variables outside this model